Genetic aspects of human prion diseases - Appleby, Brian S.; Shetty, Shashirekha; Elkasaby, Mohamed (Frontiers in Neurology, 2022)
Human prion diseases are rapidly progressive and fatal neurodegenerative conditions caused by a disease-causing isoform of the native prion protein. The prion protein gene (PRNP) encodes for the cellular prion protein, which is the biological substrate for prion disease transmission and neurotoxicity. Human prion diseases have three etiologies: sporadic, genetic, and acquired. PRNP polymorphisms and pathogenic variants play a large role in the frequency, age at onset, and clinicopathologic phenotype of prion diseases. Genetic prion diseases will be covered in detail and information necessary for clinical care, predictive genetic testing, and genetic counseling will be reviewed. Because the prion protein is necessary for transmission and neurotoxicity, many experimental treatments targeting its production are being investigated and hold potential promise as a disease modifying treatment for all forms of prion disease, including asymptomatic mutation carriers. This article will review genetic aspects of human prion disease and their influence on epidemiology, clinicopathologic phenotype, diagnostics, clinical management, and potential treatment approaches.